1977
DOI: 10.1172/jci108879
|View full text |Cite
|
Sign up to set email alerts
|

The Histocompatibility System in Juvenile, Insulin-Dependent Diabetic Multiplex Kindreds

Abstract: A B S T R A C T We have histocompatibility (HLA) genotyped 24 families with two or more juvenile, insulin-dependent, ketosis-prone diabetic siblings. This criterion for family selection was used to obtain a homogeneous form of diabetes within a sibship, because diabetes appears to be a genetically heterogeneous disease. 58 diabetic and 53 nondiabetic sibs and 40 parents were studied. 55% of the diabetic pairs were concordant for both HLA haplotypes (expected 25%), 40% were concordant for one haplotype (expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 29 publications
(37 reference statements)
2
38
0
Order By: Relevance
“…Whereas this conclusion may apply to the observations made in other groups of relatives of patients with type I diabetes, we do not believe it is relevant in our subjects, since they were selected based on variables that correlate with a lower risk for the development of type I diabetes (30) to insure that donors have normal pancreatic function before surgery. Consequently, they were older and more distant in age from the age of diabetes onset of the affected family member than were the family members included in other investigations of proinsulin in firstdegree relatives of patients with type I diabetes (4-7).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this conclusion may apply to the observations made in other groups of relatives of patients with type I diabetes, we do not believe it is relevant in our subjects, since they were selected based on variables that correlate with a lower risk for the development of type I diabetes (30) to insure that donors have normal pancreatic function before surgery. Consequently, they were older and more distant in age from the age of diabetes onset of the affected family member than were the family members included in other investigations of proinsulin in firstdegree relatives of patients with type I diabetes (4-7).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in other countries 3 - 4 have confirmed these observations, but consid-erable argument has taken place concerning the mode of inheritance of the HLA susceptibility factor. For example, some investigators favor a dominant inheritance, 5 whereas others argue that the results from family studies are compatible with an autosomal recessive pattern.…”
mentioning
confidence: 98%
“…The clinical material in 24 diabetic multiplex families and the immunological studies of the HLA have been published (1). Only the 21 families with affected members in the second generation are included in this work.…”
Section: Methodsmentioning
confidence: 99%
“…We performed this analysis only in the families without HLA recombinants, since the high frequency of recombinants in JIDD families has not been confirmed (1,8). Furthermore, we excluded another family with a homozygous parent.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation